2006
DOI: 10.1002/dmrr.613
|View full text |Cite
|
Sign up to set email alerts
|

Constant and intermittent high glucose enhances endothelial cell apoptosis through mitochondrial superoxide overproduction

Abstract: Background It has been previously shown that hyperglycemia enhances free radical production, inducing oxidative damage, which in its turn activates the death pathways implicated in cell apoptosis and necrosis. But the possible involvement of this pathway in the hyperglycemia-induced apoptosis of endothelial cells has not yet been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
184
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 290 publications
(204 citation statements)
references
References 30 publications
16
184
0
4
Order By: Relevance
“…This concept is consistent with the findings that intermittent high glucose has been shown to lead to increased damage to the endothelial cells [4][5][6][7] , mesangial cells [8] and tubulointerstitial cells [9] in culture. Brownlee et al [10][11][12] have recently proposed a "unifying mechanism" by which all the pathways involved in the pathogenesis of diabetic complications are linked through a hyperglycemia-driven intracellular excess of reactive oxygen species (ROS), superoxide anion in particular.…”
Section: Introductionsupporting
confidence: 91%
“…This concept is consistent with the findings that intermittent high glucose has been shown to lead to increased damage to the endothelial cells [4][5][6][7] , mesangial cells [8] and tubulointerstitial cells [9] in culture. Brownlee et al [10][11][12] have recently proposed a "unifying mechanism" by which all the pathways involved in the pathogenesis of diabetic complications are linked through a hyperglycemia-driven intracellular excess of reactive oxygen species (ROS), superoxide anion in particular.…”
Section: Introductionsupporting
confidence: 91%
“…T2DM is also characterized by the presence of oxidative stress (Davi et al 1999), and diabetic patients with NAFLD have higher levels of markers of oxidative stress compared to diabetic patients without NAFLD (Narasimhan et al 2010). Recently, several studies have demonstrated that IHG can generate more ROS than SHG in endothelial cells (Quagliaro et al 2003, Piconi et al 2006, islet cell (Del Guerra et al 2007, Kim et al 2012 and Schwann cells (Sun et al 2012a,b). We found that in the presence of lipotoxicity, SHG produced an increase in oxidative stress; moreover, the IHG appeared to further enhance oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic rats, pharmacological inhibition of PARP not only prevents, but also reverses endothelial dysfunction [12]. There are in vitro findings showing that oscillations in blood glucose concentration, themselves, can provoke increased free radical formation and consequent PARP activation, culminating in pathological changes in the vascular endothelium, leading to endothelial dysfunction [19,35,36]. Our in vivo findings are consistent with in vitro studies in cultured human umbilical vein endothelial cells, in demonstrating that rapid glycaemic swings result in the most substantial increase in vascular PARP activation.…”
Section: Discussionmentioning
confidence: 99%